The Impact of Milk Fat Globule Membrane with Exercise on Age-Related Degeneration of Neuromuscular Junctions - Sugita, Satoshi (Nutrients, 2021)
Morphological changes in neuromuscular junctions (NMJs), which are synapses formed between α-motor neurons and skeletal muscle fibers, are considered to be important in age-related motor dysfunction. We have previously shown that the intake of dietary milk fat globule membrane (MFGM) combined with exercise attenuates age-related NMJ alterations in the early phase of aging. However, it is unclear whether the effect of MFGM with exercise on age-related NMJ alterations persists into old age, and whether intervention from old age is still effective when age-related changes in NMJs have already occurred. In this study, 6- or 18-month-old mice were treated with a 1% MFGM diet and daily running wheel exercise until 23 or 24 months of age, respectively. MFGM treatment with exercise was effective in suppressing the progression of age-related NMJ alterations in old age, and even after age-related changes in NMJs had already occurred. Moreover, the effect of MFGM intake with exercise was not restricted to NMJs but extended to the structure and function of peripheral nerves. This study demonstrates that MFGM intake with exercise may be a novel approach for improving motor function in the elderly by suppressing age-related NMJ alterations.